A Challenge to the Obviousness of Equality of Opportunity - Matías Reeves (Mutatis Mutandis: Revista Internacional de Filosofía)
In this work, I challenge the fundamental principle of equality of opportunity, that equally talented people, whether rich or poor, should have equal opportunities to develop their talents and flourish. In this sense, I argue that: equality of opportunity is not something necessarily good in itself; it will never be achieved; and, if it were, it is not desirable. Consequently, we should think in other principle to rule our social policies. The persecution of equality of opportunity has led societies to put a lot of pressure to schools, which are seen as the social institutions to level the playing field, with the correspondent incentive to prepare students for the job market, but not for their flourishing as members of a community and the consequent loss in social cohesion.First and foremost, I will introduce several concepts of equality of opportunity, where Rawlsian fair equality of opportunity will be extended reviewed. My argument will be primarily based on two critiques: the liberal conception of the self; and the lexical priority of fair equality of opportunity over the difference principle. Then, I will show why Cohen´s currency for egalitarianism is a good alternative principle, but does not consider it implications on values such as fraternity, solidarity and empathy. In this sense, I will not only challenge Rawlsian liberals but, in some aspects, to egalitarians too. Next, my proposal is a principle that combines aspects from the debate on egalitarian currency, democratic values and communitarianism, what I call, equal access to democratic citizenship. Finally, I will present the implications over the school system if we choose to use this proposed principle rather than equality of opportunity.